2018
DOI: 10.3892/etm.2018.6306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TGF‑β1 on blood CD4+CD25high regulatory T cell proliferation and Foxp3 expression during non‑small cell lung cancer blood metastasis

Abstract: Metastatic circulating tumor cells in non-small cell lung cancer (NSCLC) metastasis have been reported to be associated with an immune response. The present study aimed to provide a theoretical basis for the immunomodulatory processes during NSCLC blood metastasis. NSCLC blood and normal peripheral blood mononuclear cells (PBMCs) were collected. The quantity of cluster of differentiation (CD)4CD25 regulatory T (Treg) cells and the intracellular forkhead box protein 3 (Foxp3) expression in CD4CD25 Treg cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…M2 macrophages promote the differentiation of Foxp3‐positive Tregs (Schmidt et al, 2016; Wynn & Vannella, 2016). TGFβ, secreted by M2 macrophages, increases the differentiation of Foxp3‐positive Tregs (Hu et al, 2018). We found that PLD1‐deficient macrophages showed augmented TGFβ expression in the M2‐polarization condition (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…M2 macrophages promote the differentiation of Foxp3‐positive Tregs (Schmidt et al, 2016; Wynn & Vannella, 2016). TGFβ, secreted by M2 macrophages, increases the differentiation of Foxp3‐positive Tregs (Hu et al, 2018). We found that PLD1‐deficient macrophages showed augmented TGFβ expression in the M2‐polarization condition (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1 inhibited antigen-specific CD8+ T-cell effector functions as demonstrated in melanoma (Ahmadzadeh and Rosenberg, 2005) and increased the number and immunosuppressive capacity of regulatory T cells (Hu et al, 2018;Huber et al, 2004;Marie et al, 2005;Polanczyk et al, 2019).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 94%
“…Hitherto, DNA constructs encoding epitopes of tumor-associated antigens have been successfully used previously (46). The following step in the development of this therapeutic approach is the creation of DNA constructs that can cover a wide range of tumor antigens, which is crucial, considering that the expression of tumor antigens may change qualitatively and quantitatively during chemotherapy and radiation therapy (47).…”
Section: Discussionmentioning
confidence: 99%